Optimization of Moringa Oleifera Leaf Extraction and Investigation of Anti Breast Cancer Activity with the Leaf Extract - Hossain, Nazia; Mirghani, M. E. S.; Raus, Raha Bt. (Engineering International, 2015)
Moringa oleifera (M. oleifera) has been considered as medicinal plant and food substance since ancient times. Nowadays various therapeutic effects of M. oleifera such as antimicrobial, anticancer, anti-inflammatory, antidiabetic, and antioxidant effects have been successfully investigated. In this study, the main objective was to optimize M. oleifera leaf-methanol extraction using Design of Experiment (DoE) software with response surface methodology in terms of temperature and incubation time by sonication. The other objective was to investigate anti-cancer activity (breast cancer cell: MCF-7) by M. oleifera methanol extraction incorporation with microtitrate tetrazolium (MTT) assay. In this research, the optimum condition for leaf extraction was found to be temperature 50⁰C and incubation time 45 min with medium frequency at sonication and it obtained 88.39% cancer cell growth inhibition by this condition. Extracted leaves inhibited MCF-7 cell line with 87.13% in average at wavelength A570nm.
Keywords: Moringa oleifera leaves extract; Breast Cancer Inhibition; Anti-cancer Activity; Optimization; Response Surface Methodology